2015
DOI: 10.1186/s12992-015-0119-7
|View full text |Cite
|
Sign up to set email alerts
|

Burgeoning burden of non-communicable diseases in Nepal: a scoping review

Abstract: In the last decades, prevalence of non-communicable diseases (NCDs) has escalated in Nepal. This study reviews existing evidence on the burden of non-communicable diseases in Nepal using the framework developed by Arksey and O’Malley for scoping reviews. A total of 110 articles were identified from database searches, and four from additional searches. The titles and abstracts were reviewed using predetermined screening criteria. We limited our search to existing literature in English language and included all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 49 publications
2
101
1
Order By: Relevance
“…5 When it comes to Nepal, the prevalence of hypertension in various parts varies between studies which ranged between 3.3% and 44.9%. [6][7][8][9][10][11][12][13][14] Furthermore a repeat cross sectional study done in a rural Kathmandu revealed that prevalence of hypertension tripled from 6% in 1980 to 18% in 2006. 12 This figure indicates that the there is burgeoning burden of hypertension in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…5 When it comes to Nepal, the prevalence of hypertension in various parts varies between studies which ranged between 3.3% and 44.9%. [6][7][8][9][10][11][12][13][14] Furthermore a repeat cross sectional study done in a rural Kathmandu revealed that prevalence of hypertension tripled from 6% in 1980 to 18% in 2006. 12 This figure indicates that the there is burgeoning burden of hypertension in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Non-communicable diseases are sweeping with an increasing trend in Nepal and hypertension is one of the most prevalent noncommunicable diseases [10]. Till now, we have not found any study has been conducted to identify the associated factors of non-adherence with the anti-hypertensive medication in Nepal.…”
Section: Introductionmentioning
confidence: 85%
“…29 As a result, there is a rapidly increasing incidence of multi-morbidity and complex medical issues associated with increasing NCDs in an aging population. 30 In industrialized countries, geriatrics and palliative care have developed as separate specialties. However, for low-and middle-income countries, this may not be a replicable model due to limitations in health resources.…”
Section: Challenges For Nepalmentioning
confidence: 99%